The Education Character through the Students’ Habit of Praying in Congregations at MA Guppi Banjarsari - Masruri, Masruri; Mustofa, Ihsan; Setiawan, Dedi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This article aims to shape the character of students, especially in overcoming moral crises. It is hoped that habits carried out consistently in the madrasah environment will stick and develop into strong characters in students. This research aims to determine the implementation of character education through the congregational prayer program at MA GUPPI Banjarsari, Way Sulan District, South Lampung Regency. This research is a qualitative descriptive study with students and teachers in Fiqh as subjects. Data collection techniques use interviews and documentation, with primary data sources coming from teachers and students. Data analysis was carried out through data reduction, data presentation, drawing conclusions, and checking the validity of the data. The research results show that the formation of students' character through the habit of praying in congregation is carried out through three main approaches, namely: a) habituation, in the form of routine implementation of religious activities; b) exemplary, in the form of real examples from teachers; and c) direction and guidance in implementing activities. The characters formed include religiousness, tolerance, discipline, hard work, friendship/communicativeness, and responsibility. Supporting factors for this activity include the availability of religious facilities and equipment, as well as the presence of a supervising teacher. This is to provide a real picture of the implementation of character education based on religious activities in madrasas, especially through the practice of congregational prayers. The results of this research can be a reference for other educational institutions in developing effective character formation strategies based on spiritual values.